Saving place : - Dobrin, Sidney I. (McGraw-Hill, 2005)
This thematically-arranged reader for first-year composition presents 56 provocative readings that encourage students to think about how they interact with the natural world and how the act of writing affects that interaction. The selections address not only traditional environmental concerns, but also issues related to recreation, survival, consumption, and other topics of interest to college students.